Pre-freezing at 10 cm above liquid nitrogen surface for eight minutes resulted the best Sapera goat semen quality - Pasha, Zehansyah Algifari; Agustono, Bodhi; Saputro, Amung Logam (Universitas Airlangga, 2022)
Sapera goat is a dairy goat resulting from a cross between a Saanen buck and an Ettawah cross doe. These small ruminants are reared by rural households for poverty reduction and undernutrition prevention. Breeding of Sapera goat through artificial insemination (AI) technique was expected to accelerate the increase in population. Unfortunately, the frozen semen of Sapera buck is not available yet. This study aims to determine the effect of the distance between semen straw and liquid nitrogen surface during pre-freezing process on the quality of frozen semen of Sapera goats. Semen was obtained from 1.5 years old Sapera buck. The ejaculates were diluted in tris-egg yolk extender to obtain a concentration of 120 x 106 spermatozoa/mL, then equilibrated at 5°C for one hour. The extended semen was packaged in 0.5 mL French straws (60 x 106 spermatozoa/straw). The filled straws were pre-frozen in the cold handling cabinet (Minitube, Germany) held at 10, 11, 12, 13, 14, and 15 cm above liquid nitrogen respectively for T1, T2, T3, T4, T5, and T6 groups, each with four replicates. After pre-freezing for eight minutes the straws were immediately plunged, and stored in liquid nitrogen (-196°C) for two days, followed by quality assessment. The best post-thawed motility (41.75 ± 2.06 %), viability (49.00 ± 0.82 %) and morphological abnormalities (4.75 ± 0.96 %) were obtained from pre-freezing stage with a distance of 10 cm. It could be concluded that in tris-egg yolk extender, post-thawed spermatozoa viability and motility of Sapera buck were qualified for AI when fresh semen was pre-frozen at 10 cm distance of straws from the surface of liquid nitrogen for eight minutes.